The Impact of Restorative Justice Programmes on Reducing Recidivism Rates in Multi-Agency Anti-Corruption Efforts - Odetunde, Adeola Isiaka; Olaoni, Simeon (African Journal of Stability and Development (AJSD), 2025)
This study examines the effectiveness of restorative justice as an alternative approach to traditional punitive measures in handling corruption cases. While punitive approaches emphasise deterrence through imprisonment and fines, restorative justice focuses on accountability, reparation, and reintegration. The study is grounded in Restorative Justice Theory, which emphasises repairing harm and fostering offenders’ accountability. Using a qualitative research methodology, the study analyses case studies, policy evaluations, and expert interviews to assess the implementation and impact of restorative justice in corruption cases. Thematic analysis is applied to identify patterns in asset recovery, voluntary disclosures, and public trust in anti-corruption institutions. Findings indicate that restorative justice can enhance transparency, increase asset recovery rates, and encourage whistleblowing. However, challenges such as political interference, legal constraints, and public perceptions of leniency hinder its effectiveness. The study concludes that while restorative justice is not a standalone solution, it serves as a valuable complement to punitive measures. Strengthening legal frameworks and institutional safeguards can enhance its role in anti-corruption efforts, making justice systems more inclusive and effective.